The evolution of the Slavic dual a biolinguistic perspective - Slobodchikoff, Tatyana G. (Studies in Slavic, Baltic, and Eastern European languages and cultures, 2019)
Developing a new theory of morphosyntactic feature economy in a morphology framework, this book uses a biolinguistic approach to examine the evolution of Slavic languages to discover how some developed a separate dual number category while others have only singular and plural and to explain the evolution of the number category in Slavic languages.